A secret never told - Noble, Shelley (Noble, Shelley. Lady Dunbridge mystery., 2021)
"Miss Fisher meets Downton Abbey in A Secret Never Told, the fourth installment in the critically acclaimed mystery series from New York Times bestselling author Shelley Noble. Philomena Amesbury, expatriate Countess of Dunbridge, is bored. Coney Island in the sweltering summer of 1908 offers no shortage of diversions for a young woman of means, but sea bathing, horse racing, and even amusement parks can't hold a candle to uncovering dastardly plots and chasing villains. Lady Dunbridge hadn't had a big challenge in months. Fate obliges when Phil is called upon to host a dinner party in honor of a visiting Austrian psychologist whose revolutionary theories may be of interest to the War Department, not to mention various foreign powers, and who may have already survived one attempt on his life. The guest list includes a wealthy industrialist, various rival scientists and academics, a party hypnotist, a flamboyant party-crasher, and a damaged beauty whose cloudy psyche is lost in a world of its own. Before the night is out, one of the guests is dead with a bullet between the eyes and Phil finds herself with another mystery on her hands, even if it's unclear who exactly the intended victim was meant to be. Worse yet, the police's prime suspect is a mystery man who Phil happens to be rather intimately acquainted with. Now it's up to Lady Dunbridge, with the invaluable assistance of her intrepid butler and lady's maid, to find the real culprit before the police nab the wrong one..."--